Doživljanje zanosa pri poučevanju pri učiteljih glasbe - Kavčič, Neža (Glasba v šoli in vrtcu, 2023)
Our research aimed to fill a void in the study of flow in Slovenian music teachers. Flow is the mental state of complete absorption, intrinsic motivation and satisfaction that overwhelms us when engaged in an activity. Since this area is still unexplored with regard to Slovenian music teachers, we chose a qualitative research method. We conducted semistructured interviews with eight music teachers (two men and six women) who work in a variety of settings. We were interested in the circumstances that lead music teachers to experience flow, how frequently it occurs, and the factors influencing the flow state. Grounded theory was used for analysis. Three main themes in music teachers‘ experiences of flow were identified: the circumstances leading to the flow state, the factors influencing the flow experience, and the relationship between the teacher‘s flow and students‘ flow.
Keywords: flow; glasba; music; music teacher; pouk; teaching; učitelj glasbe; zanos